Sufijos diminutivos y aumentativos en el discurso periodístico español: enfoque pragmático-funcional - Lesko, Khrystyna (Studia Romanica Posnaniensia, 2023)
The present article suggests a pragmatic-funcional approach to analyse diminutive and augmentative derivatives in Spanish newspapers ABC, El Mundo and El País. More specifically, the focus of interest is on studying their connotative meanings (emotional and expressive). Special attention is paid to the syncretic meaning of the investigated derivatives according to the context in which they appear. The polysemic character of diminutives and augmentatives constitutes a problem when it is necessary to identify their true meaning. In this case, linguistic and extralinguistic factors (social and cultural) should be considered.